Respuesta :

Answer:

x = -3

Step-by-step explanation:

Solve for x:

4 x - 2 x - 2 = x - 5

Grouping like terms, 4 x - 2 x - 2 = (4 x - 2 x) - 2:

(4 x - 2 x) - 2 = x - 5

4 x - 2 x = 2 x:

2 x - 2 = x - 5

Subtract x from both sides:

(2 x - x) - 2 = (x - x) - 5

2 x - x = x:

x - 2 = (x - x) - 5

x - x = 0:

x - 2 = -5

Add 2 to both sides:

x + (2 - 2) = 2 - 5

2 - 2 = 0:

x = 2 - 5

2 - 5 = -3:

Answer:  x = -3

Answer:

x = -3

Step-by-step explanation:

first you would want to arrange the equation according to the variables so,

4x - 2x - x =2 - 5

Now solve,

1x = = -3

x = -3

Hope this helps :)